Building a development-friendly world trading system - Kumar, Nagesh (2007)
Makes some specific proposals on how to build a more sustainable and development-friendly world trading system. Suggests that the current impasse in the Doha Round talks should be seen as an opportunity for developing countries to work on building consensus within their ranks, so that agreed-upon development issues can be effectively brought to the table on the appropriate occasion.